A Swelling over Sternum in a Child: Reminder of an Uncommon Diagnosis - Pradnya Joshi; Sandeep B. Bavdekar; Sushma U. Save (Case Reports in Pediatrics)
Lack of awareness about isolated tubercular osteomyelitis of the sternum resulted in a delay in diagnosing the condition in an eleven-year-old girl who presented with a gradually increasing swelling over the sternum. Radiological, histological, and microbiological investigations helped diagnose the condition and the child responded well to antitubercular therapy (ATT) and surgical debridement. The report provides a brief description about the various management options available.